Growth parameters, longevity, and mortality of the seabob shrimp Xiphopenaeus spp. (Decapoda: Penaeidae) in four important fishing regions of southeastern Brazil - Miazaki, Lizandra Fernandes [UNESP] (2021)
We investigated and compared growth parameters, longevity, mortality (total, natural, and fishing), and exploitation rates of the seabob shrimp Xiphopenaeus spp. in four important fishing regions of southeastern Brazil. The hypothesis that the growth and mortality characteristics of distinct populations differ along a latitudinal gradient was tested. Sampling was performed monthly in Macaé, Ubatuba, Santos/São Vicente, and Cananéia over a 1- to 2-year period. Growth and longevity parameters were estimated by the von Bertalanffy growth equation models. Total mortality (Z) was estimated by length-converted catch curves. Growth parameters differed between sexes: males reached smaller sizes, showed larger growth coefficients (k) and higher mortality, and lived less than females in the four studied regions. Rather than finding a latitudinal gradient, our results support the hypothesis that distinct local environmental characteristics and fishing pressures alter the growth and population dynamics of Xiphopenaeus spp. in different areas. Our study indicates that the stocks of Xiphopenaeus spp. are overexploited, highlighting the importance of management plans to prevent the collapse of stocks and maintain them at sustainable levels for long-term exploitation.